An overview of Indonesian regulatory framework on Islamic financial technology (fintech) - Mahdiah Aulia; Aulia Fitria Yustiardhi; Reni Oktavia Permatasari (Jurnal Ekonomi & Keuangan Islam, 2020)
The advancement of technology has touched many sectors, including financial industries. The emergence of Financial Technology or Fintech has changed the way people do business transactions. Indonesia as a country with a separate regulatory model under the Central Bank of Indonesia (BI) and Financial Services Authority (OJK) has issued several regulations to regulate fintech, which includes Islamic fintech. This paper aims to analyse the existing regulatory framework of Islamic fintech in Indonesia and gives some recommendations, if any, to improve Islamic fintech development in Indonesia. It uses qualitative methodology by extracting information from works of literature and existing regulations. This research finds that both BI and OJK have significant roles in regulating Islamic fintech without issuing any provision to address it specifically. However, it is complemented by the fatwa issued by the National Shariah Board of Indonesian Ulama (DSN MUI).